GENERAL RULES FOR IMPOSING A SENTENCE OF JUVENILE IMPRISONMENT (EU and comparative law issues and challenges series (ECLIC), 2018)
Sentence of juvenile imprisonment is analyzed in its theoretical aspect and then in the aspect of legislative regulation in positive criminal legislation. Taking into consideration the content and legal nature, in practice this subject is mainly defined through criminal law in its material aspect, with certain explanation of those questions that are related to procedural and executive law to that level which the subject of investigation allows. In the perspective of criminal law, the legal terms in both national and comparative juvenile legislation are analyzed, in order to determine the complete sense and justification of the punishment. The analysis is done through interrelations of juvenile imprisonment sentence and certain institutes of criminal law, then relevant theoretical and practical concepts and discussions. Normative aspect aims to better explain the content and function of this punishment based on certain legal modification both in national and in comparative law, especially in European criminal legislation. Criminal justice analysis of the terms of juvenile court, contributes to clear differentiation from other criminal sanctions, above all, corrective measures, with special effect on its practical use. The investigation made in regards to the content, conditions of passing and justification of juvenile imprisonment sentence provides certain knowledge of its efficacy and justification in the system of criminal sanctions. The necessity of studying general and specific circumstances for its imposing contributes to more complete approach to the discussions both in the theory and court practice. Allowing the possibility that the sentence of juvenile imprisonment is only imposed on senior juveniles, simultaneously leads us to think that a special attention will be paid to two groups of circumstances: level of maturity and necessary time for both behavioral and professional education of the juvenile. In parallel to this aspect, some other questions appearing both in theoretical and practical aspect of this serious and only punishment have been discussed.